Beta‐blocker‐associated hypoglycaemia: New insights from a real‐world pharmacovigilance study. Issue 8 (23rd February 2021) - Carnovale, Carla; Gringeri, Michele; Battini, Vera; Mosini, Giulia; Invernizzi, Elena; Mazhar, Faizan; Bergamaschi, Francesco; Fumagalli, Mara; Zuccotti, Gianvincenzo; Clementi, Emilio; Radice, Sonia; Fabiano, Valentina
Abstract : Aims: To investigate the statistical association between hypoglycaemia and β‐blocker use and to define what patient and drug characteristics could potentially increase the risk for its occurrence. Methods: We investigated the relationship between pharmacological parameters of β‐blockers and the occurrence of hypoglycaemia by conducting a case/non case analysis using the Food and Drug Administration Adverse Event Reporting System database. Pharmacological properties that could represent a predictive factor for hypoglycaemia were analysed through a multilinear binary logistic regression (null hypothesis rejected for values of P < .05). We also performed a systematic review of clinical studies on this association. Results: Of 83 954 selected reports, 1465 cases (1.75%) of hypoglycaemia were identified. The association was found statistically significant for nadolol (reporting odds ratio [95% confidence interval]: 6.98 [5.40–9.03]), celiprolol (2.35 [1.35–4.10]), propranolol (2.14 [1.87–2.46]) and bisoprolol (1.42 [1.25–1.61]). Paediatric cases ( n = 310) showed a positive association with hypoglycaemia for long half‐life drugs (odds ratio [95% confidence interval]: 2.232 [1.398–3.563]) and a negative association for β1‐selectivity (0.644 [0.414–0.999]). Seven papers were included in the systematic review. Because of great heterogeneity in study design and demographics, hypoglycaemia incidence rates varied greatly among studies, occurring in 1.73% of the cases for propranolol treatment ( n total participants = 575), 6.6% for atenolol ( n = 30) and 10% for carvedilol ( n = 20). Conclusion: Nadolol appears to be the β‐blocker significantly most associated with hypoglycaemia and children represent the most susceptible sample. Furthermore, long half‐life and nonselective β‐blockers seem to increase the risk for its occurrence.